Jesús Ponce Cárdenas, La imitación áurea (Cervantes, Quevedo, Góngora), París, Éditions Hispaniques, 2016, 283 pp. ISBN 978-2-85355-083-3 (Minerva, 2019)
Review: Jesús Ponce Cárdenas, La imitación áurea (Cervantes, Quevedo, Góngora), París, Éditions Hispaniques, 2016, 283 pp. ISBN 978-2-85355-083-3